Bertahan dari Krisis 1998 hingga Pandemik: Usaha Dodol Deli Pasar Bengkel Tak Pernah Goyah - Dini Dwi Wahyuningsih; Ratna Sari Dewi; Rany Aprilliana; Ananda Nirmala; Wanda Riana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to describe the success strategy of the Dodol Deli business, an MSME that has existed since 1988 in Pasar Bengkel, Serdang Bedagai Regency. This business is an example of traditional business resilience in the face of various economic challenges, ranging from the 1998 monetary crisis, road infrastructure development, to the COVID-19 pandemic. This research uses a descriptive qualitative method with a case study approach, through direct interviews with business owners. The results show that the success of Dodol Deli is influenced by strong entrepreneurial character, product innovation, efficient production management, and adaptive marketing strategies, including the utilization of social media. In addition, the decision not to use preservatives and not to rely on modern retail systems is an added value in maintaining product authenticity and customer loyalty. Dodol Deli also demonstrates healthy self-financing practices and receives support through non-cash assistance from the government. These findings reinforce the importance of a combination of local values, business independence, and technological adaptation as keys to MSME sustainability.